Real‐World Effectiveness of Initial Disease‐Modifying Therapies in Pediatric Multiple Sclerosis. Issue 1 (14th May 2020) - Krysko, Kristen M.; Graves, Jennifer S.; Rensel, Mary; Weinstock‐Guttman, Bianca; Rutatangwa, Alice; Aaen, Gregory; Belman, Anita; Benson, Leslie; Chitnis, Tanuja; Gorman, Mark; Goyal, Manu S.; Harris, Yolanda; et al.
Abstract : Objective: To assess real‐world effectiveness of initial treatment with newer compared to injectable disease‐modifying therapies (DMTs) on disease activity in pediatric multiple sclerosis (MS) and clinically isolated syndrome (CIS). Methods: This is a cohort study of children with MS/CIS followed at 12 clinics in the US Network of Pediatric MS Centers, who received initial therapy with newer (fingolimod, dimethyl fumarate, teriflunomide, natalizumab, rituximab, ocrelizumab) or injectable (interferon‐β, glatiramer acetate) DMTs. Propensity scores (PSs) were computed, including preidentified confounders. Relapse rate while on initial DMT was modeled with negative binomial regression, adjusted for PS‐quintile. Time to new/enlarging T2‐hyperintense and gadolinium‐enhancing lesions on brain magnetic resonance imaging were modeled with midpoint survival analyses, adjusted for PS‐quintile. Results: A total of 741 children began therapy before 18 years, 197 with newer and 544 with injectable DMTs. Those started on newer DMTs were older (15.2 vs injectable 14.4 years, p = 0.001) and less likely to have a monofocal presentation. In PS‐quintile–adjusted analysis, those on newer DMTs had a lower relapse rate than those on injectables (rate ratio = 0.45, 95% confidence interval (CI) = 0.29–0.70, p  < 0.001; rate difference = 0.27, 95% CI = 0.14–0.40, p = 0.004). One would need to treat with newer rather than injectable DMTs for 3.7 person‐years to prevent 1 relapse. Those started on newer DMTs had a lower rate of new/enlarging T2 (hazard ratio [HR] = 0.51, 95% CI = 0.36–0.72, p  < 0.001) and gadolinium‐enhancing lesions (HR = 0.38, 95% CI = 0.23–0.63, p  < 0.001) than those on injectables. Interpretation: Initial treatment of pediatric MS/CIS with newer DMTs led to better disease activity control compared to injectables, supporting greater effectiveness of newer therapies. Long‐term safety data for newer DMTs are required. ANN NEUROL 2020 ANN NEUROL 2020;88:42–55